An Account of the Early-winter Migrant and Resident Birds in a Wetland Habitat of the Indian Wild Ass Sanctuary in the Dasada Taluka, Surendra Nagar, Gujarat - Chatterjee, Abhishek; Ghoshal, Sudeshna; Chakrabarti, Pinakiranjan (Indian Forester, 2018)
The Indian Wild Ass Sanctuary, although famous for conserving the endemic Asiatic Wild Ass, is also an Important Bird and Biodiversity Area (IBA site) as It Is a wintering and breeding site for many migrant birds. This study aims to record the structural aspects of the regional bird community during early migration season. Authors have surveyed a particular site during November-December months for three consecutive years (2013- 2015). A total of 79 bird species belonging to 63 genera and 36 families have been recorded using point count, line transect, night surveys and opportunistic encounters. Among all recorded species, the Lesser Flamingo was most abundant. An increase in species richness is likely to occur later in the migration season upon further arrival of immigrant avifauna. The recorded species abundance distribution of this community is a perfect fit with the log-normal model. This proves an equitable distribution of individuals among different species of tills community and also testifies of its high diversity. After studying the feeding guild composition, fourteen different shared feeding guilds were identified, among which the Insectivorous guild was most abundant. Through this study, it can be said that this habitat has been well conserved over the years. Extensive surveys in different sites of this sanctuary need to be conducted, to assess the need for revising current conservation protocols.